POTENSI HUTAN TANAMAN JATI DALAM PERENCANAAN PEMBANGUNAN WILAYAH KABUPATEN MUNA - La Ode Agussalim Mando; Ris Hadi Purwanto (Universitas Haluoleo, 2015)
The research seeks to develop engineering models of teak plantation forest development plans. Sampling was carried out by farmers and teak stand intentionally (purposive sampling). The results showed that the potential of teak forest planting protected areas : basal area of 31.4109 m2/ha, the standing stock is 597.5083 m3/ha. Production forests : basal area of 2.5975 m2/ha, the standing stock is 12.8025 m3/ha. Meanwhile, for the community forests : basal area of 17.8533 m2/ha, the standing stock is 267.8002 m3/ha. The recommendations teak forest development planning model that is implementation of Management Regimes (MR) V on Mata Kidi protected areas, MR II and III on production forests and Conventional MR on community forests. Key words : potential, teak forests, planning, management regimes